2017
DOI: 10.2135/cropsci2016.04.0271
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Chinese and Global Pea (Pisum sativum L.) Collections

Abstract: Pea (Pisum sativum L.) is an important food and feed legume grown across many temperate regions of the world, especially from Asia to Europe and North America. The goal of this study was to use 30 informative pea microsatellite markers to compare genetic diversity in a global core from the USDA and a core collection from the National Genebank of China (NGC). The Chinese and global collections had 295 and 305 accessions, respectively. A total of 259 alleles were detected in the full 600 accessions, with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 46 publications
(62 reference statements)
4
11
0
Order By: Relevance
“…Although the research area where the landraces were collected in the current study does not cover a wide region, our results revealed that either similar or higher diversity results were obtained compared to studies that collected landraces from wider regions. In terms of PIC and allele numbers, the same results were obtained by Sarikamis et Moreover, the average PIC and allele values obtained in this research were higher than in the studies conducted by Handerson et al (2014) and Jain et al (2014) and were similar to studies done by Cupic et al (2009), Cieslarova et al (2012, Ahmad et al (2015), Baloch et al (2015), Prakash et al (2016), Nisar et al (2017), Wu et al (2017), and Uysal et al (2018). On the other hand, lower average PIC and allele values were observed in this study compared to those performed by Smýkal et al (2008b) and Rana et al (2017).…”
Section: Discussionsupporting
confidence: 91%
“…Although the research area where the landraces were collected in the current study does not cover a wide region, our results revealed that either similar or higher diversity results were obtained compared to studies that collected landraces from wider regions. In terms of PIC and allele numbers, the same results were obtained by Sarikamis et Moreover, the average PIC and allele values obtained in this research were higher than in the studies conducted by Handerson et al (2014) and Jain et al (2014) and were similar to studies done by Cupic et al (2009), Cieslarova et al (2012, Ahmad et al (2015), Baloch et al (2015), Prakash et al (2016), Nisar et al (2017), Wu et al (2017), and Uysal et al (2018). On the other hand, lower average PIC and allele values were observed in this study compared to those performed by Smýkal et al (2008b) and Rana et al (2017).…”
Section: Discussionsupporting
confidence: 91%
“…Jing et al (2010) studied the genetic diversity of 3020 Pisum accessions using RBIP markers, which separated the landraces, cultivars and wild Pisum accessions into distinct groups, and provided a framework for designing core collections. Genetic variation of pea accessions based on SSR markers has also been reported in other studies and the test accessions were clustered into distinct gene pools (Kumari et al, 2013; Jain et al, 2014; Rana et al, 2017; Wu et al, 2017).…”
Section: Introductionsupporting
confidence: 71%
“…However, few (less than 1%) of these are wild pea relatives [ 52 ]. Molecular analysis of pea diversity preserved in germplasm collections has been carried out using various methods [ 30 , 31 , 33 , 35 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Recently, genotyping-by-sequencing was applied [ 61 ] to a set of 431 P. sativum ( sensu lato ) accessions, including 11 P. sativum subsp.…”
Section: Introductionmentioning
confidence: 99%